Problem Solving Training for Veterans with Complex Comorbidities: Treatment Delivery Adaptations during COVID-19. Issue 1 (1st January 2022) - Beaudreau, Sherry A.; Otero, Marcela C.; Walker, Jessica A.; Gould, Christine E.; Sisco, Shannon; White, Patricia; Pella, Kaycie; Wiley, Elizabeth; Voorhees, Kathryn; Wetherell, Julie Loebach
ABSTRACT: Objectives: To summarize adaptations due to COVID-19 for VA Problem Solving Training (PST) for clinicians serving medically complex patients and to compare patient mental health outcomes in the year before (2019) and during COVID-19 (2020). Methods: Clinicians attended a multi-day workshop and up to 6 months of small-group consultation for two training cases. In 2019 and 2020, 122 Veteran patients completed baseline and posttreatment measures of depression (Patient Health Questionnaire-9), anxiety (Generalized Anxiety Disorder-7 item), and negative problem-solving beliefs (Negative Problem Orientation Questionnaire). Qualitative data were collected on clinician's pandemic-related treatment implementation challenges. Results: Program adaptations during COVID-19 addressed challenges due to delivering treatment by telephone, video, or in person; Veteran patient recruitment barriers; and privacy issues for telephone and video. Veterans in both pre-pandemic and COVID-19 cohorts had significant improvements in depression, anxiety, and negative problem-solving beliefs, with no significant differences in the amount of improvement between the two cohorts. Conclusions: Flexibilities afforded to clinicians delivering the PST training program during the pandemic addressed key obstacles and barriers to recruitment, and implementation did not diminish the effectiveness of the intervention. Clinical implications: Findings support continued implementation of the PST training program with added flexibility to treatment delivery beyond the pandemic.